THE EFFECT USING OF DIFFERENT COWS MANURE LEVELS AND RICE HUSK ON THE QUALITY OF BIOARANG BRIQUETTES PRODUCED - Gerson Frans Bira; Paulus Klau Tahuk; Yosef J. Mau (Journal of Tropical Animal Science and Technology, 2020)
Energy is a crucial problem because it is inversely proportional to the rapid population growth. As a result, energy reserves are running low, especially fossil energy. For this reason, innovation is needed to provide alternative fuels to address household energy needs. One alternative fuel to overcome household energy needs. Briquette can be used as an alternative fuel which is expected to be able to overcome the energy crisis because it comes from materials that are around. Utilization of livestock and agricultural waste is one alternative that is very appropriate to overcome rising prices and oil fuel shortages. Utilization of waste and use of renewable energy needs to be integrated. In this study aims to utilize waste into renewable energy. The method used in this study was a completely randomized design (CRD) with 4 treatments and which were repeated 4; R1:80% cows manure charcoal + 15% Rice husk charcoal + 5% Starch flour, with treatment R2: 70% Cows manure charcoal + 25% Rice husk charcoal + 5% Starch flour; R3: 60% Cows manure charcoal + 35% Rice husk charcoal + 5% Starch flour; R4: 50% Cows manure charcoal + 45% Rice husk charcoal + 5% Starch flour. The composition of the four briquettes has the same density (100g) with a pressure of 30 kg/cm2. The variables studies observed were water content, ash content, combustion rate and heating value. The data obtained were processed using variance according o the Completely Randomized Design (CDR) and Duncan's multiple range test. The results showed that the use of cows manure charcoal and rice husk with different levels had a significant effect (P<0.05) on the variables studied. It was concluded that the use of 50% cows manure charcoal, 45% rice husk charcoal, and 5% starch produced the best quality briquettes with a moisture content of 3.11%, ash content of 23.72%, burning rate of 0.26 g/sec and heating value 1247 cal/g.